The Relationship Of Grade 7 Students’ General Ict Use And Attitudes Towards Ict Use For School Related Activities With Ict Self-Efficacy In Eleven English Program Schools Of Thailand - Hines, Michael G.; Lynch, Richard (Scholar: Human Sciences, 2019)
The purpose of this study was to determine the relationship of Grade 7 students’ general ICT use and attitudes towards ICT use for school-related activities to ICT self-efficacy in eleven English Program schools of Thailand. An adapted version of the OECD Programme for International Student Assessment 2012, Information and Communication questionnaire was used to collect data from 559 Grade 7 English Program (EP) secondary students attending public or private (i.e., non-international) secondary schools within Central Thailand who were enrolled in an English Program during the first term of the 2017-2018 academic school year. Descriptive statistics and multiple correlation coefficients were used to analyze the data. To encourage self-access learning and provide the type of communicative and collaborative tools to EP students that promote 21st century learning skills, this researcher developed a Learning Management System (LMS) system, Icon Educate. Every incoming Grade 7 class enrolled in a participating English Program was given training on how the system can be used as well as an introduction to its content. It was found that there was a strong and positive relationship between students’ general ICT use for school-related activities and their attitudes towards ICT use for school-related activities. Additionally, there was a moderately strong and negative relationship between students’ general ICT use for school-related activities and their CT self-efficacy.